PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XI IIS DALAM MATA PELAJARAN EKONOMI DI SMA N 5 SURAKARTA TAHUN AJARAN 2015/2016 - Muhammad Andi Auliya Hakim; Sunarto Sunarto; Salman Alfarisy Totalia (Department of Economics Education, Universitas Sebelas Maret, 2016)
The purpose of this research is to improve learning outcomes of student in economic lesson at class XI IIS 1 of Senior High School 5 Surakarta in the academic year of 2015/2016 with the implementation of Problem Based Learning (PBL) model.The type of this research is classroom action research. The subject of this research is students at XI IIS 1 of Senior High School 5 Surakarta in the academic year of 2015/2016 with 31 students. The data sources are from the teacher and students. The technique of data collection used are, (a) observation, (b) interview, (c) documentation, and (d) test. Validity of data used is triangulation resources and method. Comparative statistic analysis, analysis of quantitative data, and analysis of qualitative data is used for analyzing the data. The procedures of this research are (a) planning, (b) action, (c) observation, and (d) reflection.Based on the research results, the learning process with the implementation of Problem Based Learning (PBL) model can improve learning outcomes of students. It was proven in the cycle I that students learning outcomes were increased 4,07 (average score of pre cycle 72,90 and average score of the cycle I 76,97) and percentage of minimal prerequisite score is increased 9,67% (percentage of pre cycle 61,29% and cycle I 70,96%). On the cycle II, students’ learning outcomes on cycle II also increased 6,68 (average score of cycle I 76,97 and average score of the cycle II 83,65) and percentage of minimal prerequisite score increased 16,13% (percentage of cycle I 70,96% and cycle II 87,09%).The conclusion of this research is that the implementation of Problem Based Learning (PBL) model can increase learning outcomes of student in Economic lesson at XI IIS 1 of Senior High School 5 Surakarta, in the academic year of 2015/2016.